KEYS TO SUCCESS IN ADVANCING TO EXPERT AND SENIOR EXPERT RANKS IN EDUCATIONAL ADMINISTRATION - Samkumuang, Boontarika; Buasuwan, Prompilai; Sarnsawang, Sudarat (Journal of Education and Innovation, 2025)
This study aimed to 1) explore the perspectives of educational administrators under the Bangkok Metropolitan Administration (BMA) regarding professional advancement; 2) examine the motivations and challenges faced by these administrators to pursue professional advancement to expert and specialist levels in educational administration; and 3) investigate the academic work development guidelines followed by educational administrators under the BMA for achieving expert and specialist status. The research employed a qualitative methodology, utilizing a multiple case study approach. Six educational institution directors—three with expert qualifications and three with specialist qualifications—were purposively selected from BMA-affiliated schools. Data were collected through document analysis content analysis and in-depth interviews, with the quality of the findings was ensured by applying Lincoln and Guba’s trustworthiness criteria. The findings revealed as follows: 1) The perspectives of educational administrators on professional advancement were shaped by their self-confidence, performance expectations, and personal goal setting; 2) the motivations and challenges associated with attaining expert and specialist status were influenced by their needs for existence, relationships, and growth; and 3) the academic work development process comprised three key phases: Phase 1: Preparation—defining clear objectives, analyzing the context, and selecting relevant research topics; Phase 2: Execution and Development—conducting research and developing academic outputs; and Phase 3: Review—evaluating and refining the completed work.